2006
DOI: 10.1509/jmkr.43.1.121
|View full text |Cite
|
Sign up to set email alerts
|

Household Life Cycles and Lifestyles in the United States

Abstract: Household life cycle has been widely used as a determinant of consumer behavior and a basis for market segmentation. However, there is considerable disagreement about how life stages should be defined and how households progress through these stages. Existing studies use a priori definitions, which are tested on a cross-sectional survey of households collected at a single point in time and thus cannot reveal the real dynamics of the household life cycle. The Panel Study of Income Dynamics provides longitudinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
86
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(88 citation statements)
references
References 22 publications
1
86
0
1
Order By: Relevance
“…First, this article shows that customer income influences the degree of mental budgeting and, as a result, how customers align their future purchase behavior to budgets they set for particular categories of expenses. However, the degree to which customers engage in budgeting could be affected by additional factors such as the customer's stage in the life cycle (Du & Kamakura, 2006. For example, customers with young children might engage in mental budgeting to a higher extent than customers with no or adult children.…”
Section: Discussionmentioning
confidence: 99%
“…First, this article shows that customer income influences the degree of mental budgeting and, as a result, how customers align their future purchase behavior to budgets they set for particular categories of expenses. However, the degree to which customers engage in budgeting could be affected by additional factors such as the customer's stage in the life cycle (Du & Kamakura, 2006. For example, customers with young children might engage in mental budgeting to a higher extent than customers with no or adult children.…”
Section: Discussionmentioning
confidence: 99%
“…Danko and Schaninger, 1990;Douthitt and Fedyk, 1988;Douthitt and Fedyk, 1990;Du and Kamakura, 2006;Fritzsche, 1981;McLeod and Ellis, 1982;Putler et al, 2007;Redondo-Bellón et al, 2001;Wagner and Hanna, 1983;Schaninger and Danko, 1993;Wells and Gubar, 1966;Wilkes, 1995). Most of these studies examine the effects of household life cycle on product category buying behavior.…”
Section: Introductionmentioning
confidence: 99%
“…These and other life cycle studies (e.g. Du and Kamakura, 2006) have consistently shown that identifying the phase of a life cycle is a critical precursor to using the life cycle for forecasting purposes.…”
Section: Introductionmentioning
confidence: 77%